Factors of Seeking Professional Psychological Help by the Bereaved by Suicide - Geležėlytė, Odeta; Gailienė, Danutė; Latakienė, Jolanta; Mažulytė-Rašytinė, Eglė; Skruibis, Paulius; Dadašev, Said; Grigienė, Dovilė (Frontiers in Psychology, 2020)
Background: Studies show that people bereaved by suicide often feel a strong need for professional help. It is hypothesized that aspects related tosuicide bereavement, such as stigmatization, shame or guilt, hinder help-seeking process of the bereaved. However, little is known about help-seeking behaviors of people who has lost someone due to suicide. Aims: this study was conducted to attain a better understanding of the contributing factors, including the specific features of grief following suicide, to help-seeking behaviors of the bereaved by suicide. Methods: The sample consisted of 82 adults bereaved by suicide (64 female; average age 37.79, SD=14.33). Instruments assessing stigmatization, shame, guilt levels, well-being, tendency to disclose emotional distress and attitudes towards seeking professional psychological help were used. The participants were also asked an open-ended question what professional help-seeking barriers they had encountered. Comparisons between the groups, logistic regression analysis and thematic analysis of the qualitative data were performed. Results: The findings revealed that bereaved participants who sought professional psychological help reported experiencing stigmatization and feeling guilty after the loss significantly more often. Also the results showed that attitudes towards mental health specialists had the highest prognostic value in predicting help-seeking behaviors of the bereaved. The participants themselves identified the gaps in the health care system as main barriers to seeking help. Conclusion: The results challenge previously spread notion that stigmatization, guilt and shame after suicide can act only as help-seeking barriers.